Pelatihan Guru SD di Tangerang: Implementasi TPR dalam Meningkatkan Penguasaan Bahasa Inggris - Ishak Ishak; Euis Yanah Mulyanah (Universitas Lancang Kuning, 2020)
This Community Service aims to motivate and improve English teachers' skills, especially in the area of ​​Tangerang Regency. Tangerang Regency is lower than the Tangerang city area. Based on Mulyanah's research from the University of Muhammadiyah Tangerang in 2018, there were 26% differences in English students' proficiency between the regency and city areas; this was seen in the scores of students' mastery of English in the two regions. From the research, problems were found, one of them, the teacher's lack of competence of English proficiency it caused by non-linear fields of science. Based on this problem, teachers need English training in the region. The participants were attended by 20 English teachers who were in the Paku Haji district-Tangerang. The training is divided into several of processes, namely a preliminary test to determine initial ability, and then given six times of training which is to train teachers using the Total Physical Responses (TPR) method by using English Instructions in the teaching-learning process, finally is final test to know the final ability after training given. The results of the training are 1) Increased teacher motivation in learning English, 2) Increased confidence using English both in the classroom and outside the classroom, 3) Increased teacher competence in their English subjects.